MODEL KONSEPTUAL MEDIA MOTION GRAPHIC INTERAKTIF MATEMATIKA UNTUK SISWA KELAS V SEKOLAH DASAR - Titik Putri Wardaniasih; Siti Rohmi Yuliati; Ika Lestari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2020)
Abstract: The purpose of this research is to find a conceptual model as a basic in developing a learning media Mathematics of Scale material using motion graphic media. The development model used in this research is Hannapin and Peck's model which is consists of three stages, namely requirements analysis, design, and development or implementation. This research was conducted at SDN Karanggan 01 Gunung Putri, Bogor towards fifth grade students of elementary schools. The results of the product feasibility trial show that interactive motion graphic media is very feasible to use by obtaining an average expert review rating of 95.14% with the category